Hesperitin Synergistically Promotes the Senescence Induction of Pentagamavunone-1 in Luminal Breast Cancer Cells, T47D - Rifai, Fauziah Novita Putri; Hanifa, Mila; Zulfin, Ummi Maryam; Ikawati, Muthi; Meiyanto, Edy (Universitas Gadjah Mada, 2024)
Pentagamavunone-1 (PGV-1), a curcumin analog, is a promising anticancer candidate for several cancers that have been proven in vitro and in vivo. However, the efficacy of PGV-1 against breast cancer is subject to improvement to achieve a more suitable application. Here we propose hesperitin, a citrus flavonoid, to increase the anticancer potency of PGV-1 in luminal breast cancer cells. We use the T47D cell as the model to investigate the effect of co-administration of PGV-1 and hesperitin on cell cycle block, apoptosis modulation, and senescence phenomena. PGV-1 and hesperitin showed strong and weak cytotoxicity with an IC50 value of 2 µM and 100 µM, respectively. The co-treatment of PGV-1 and hesperitin resulted in strong synergistic effects with combination index (CI) value of ≤ 0.2. This combination caused apoptosis in correlation with cell cycle disruption in G2/M phase at 48 h. In particular, PGV-1 and hesperitin combination increased the incidence of cellular senescence significantly higher than the single treatment. Despite its senescence potentiation, hesperitin did not induce senescence in normal cells. Taken together, hesperitin may increase the anticancer potency of PGV-1 by modulating cell cycle arrest and apoptosis via the senescence mechanism.